Tensile behavior and inelastic strain recovery of Cu-Co nanolaminates. (May 2021) - Berlia, Rohit; Rasmussen, Paul; Yang, Shize; Rajagopalan, Jagannathan
Abstract: The mechanical response of macroscale metallic samples is typically determined using the uniaxial tensile test, which provides a direct measure of critical properties such as Young's modulus and yield strength. However, due to experimental challenges, uniaxial tensile tests have seldom been used for studying the mechanical behavior of metallic nanolaminates. Here, we use a custom-made MEMS device to study the quasi-static, uniaxial tensile behavior of Cu-Co nanolaminates with four different layer thicknesses ( h = 2, 4, 8 and 16 nm). Our experiments reveal a peak in the yield strength at h = 4 nm, while the Young's modulus is independent of h . Surprisingly, the nanolaminates recover significant amount (> 60%) of inelastic deformation during and after unloading, and this recovery is enhanced by an increase in temperature. Possible mechanisms for this unusual strain recovery in Cu-Co nanolaminates are discussed. Graphical abstract: Image, graphical abstract